Г.НУРЛЕПЕСОВАНЫҢ «ҚУМАР АНА» ДӘСТАНЫНДА ТАРИЙХЫЙ ОБРАЗЛАРДЫҢ СӘЎЛЕЛЕНИЎИ - Оразбаева, Г. (ILIM hám JÁMIYET, 2018)
The article deals with the skill of Gulnara Nurlepesova in creating historical images using the artistic method in the narration of events. The characters of the brave girls in the epos «Kumar ana» have been studied comparatively with the characters of historical persons from the epos.